2018
DOI: 10.21511/ppm.16(3).2018.19
|View full text |Cite
|
Sign up to set email alerts
|

Corporate diversity and corporate social environmental disclosure of listed manufacturing companies in Nigeria

Abstract: This study examined the impact of corporate diversity on corporate social environmental disclosure of registered manufacturing firms in Nigeria. The study considered both industrial and consumer goods firms, respectively, consisting a total of 37 firms. A total of 17 firms was selected for this study using purposive random sampling spanning the period 2012–2016. While the content analysis technique was engaged to ascertain the extent of corporate social environmental disclosure, the study adopted the following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…It is a yardstick to attain if the data suffer any form of multicollinearity and to explore any possible association amid variables. However, the summary of this table proves that the correlation between construct does not exceed the 80% threshold as inferred in Ozordi et al (2018). Hence, it proves the absence of multicollinearity.…”
Section: Methodsmentioning
confidence: 57%
“…It is a yardstick to attain if the data suffer any form of multicollinearity and to explore any possible association amid variables. However, the summary of this table proves that the correlation between construct does not exceed the 80% threshold as inferred in Ozordi et al (2018). Hence, it proves the absence of multicollinearity.…”
Section: Methodsmentioning
confidence: 57%
“…Gender diversity of board members is expected to have a positive impact on corporate social responsibilities. Previous research has shown that having female members on the board of directors has positively influenced corporate sustainability performance (Emmanuel et al, 2018;Margaretha and Isnaini, 2014). Females generally contribute more to social intelligence and collaborative decision making as compared to their male counterparts (Bart and Mcqueen, 2013;Harjoto et al, 2015).…”
Section: Board Diversitymentioning
confidence: 94%
“…Therefore, much empirical research has been conducted that shows a positive relationship between independent directors and CSR (Barako and Brown, 2008;Ho and Wong, 2001). However, there might be a negative relationship between independent directors and corporate sustainability reporting due to other influential factors such as regulatory pressure on voluntary disclosure, boards' lack of expertise, and their newness to the business model (Emmanuel et al, 2018).…”
Section: Board Independencementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, women presence on board is related to greater corporate innovation success [18]. Also, women on board are influential in disclosing corporate and social activities [19]. Contrary, female director do not matter in improving firm performance [20].…”
Section: Introductionmentioning
confidence: 99%